(untitled) (The Journal of Psychology and Sociology, 2015)
The article analyzes the current, but so far raises the problem of profes sional deformation of the person of employees of the penitentiary system. With the assistance of extensive theoretical material factors considered burnout employees, as well as the main directions of work with him.